The impact of the global tax reforms on Ireland's attractiveness to foreign direct investment and the wider economy - Iulia Siedschlag; Juan David Durán; Robert McLoughlin; Daire De Hora (The Economic and Social Research Institute (ESRI), 2023)
This paper explores the possible effects of the global tax reforms on Ireland's attractiveness to foreign direct investment (FDI) and FDI-related employment. We use data on new greenfield FDI in Ireland and other EU countries over 2011-2020 and estimate a range of possible outcomes on Ireland's attractiveness to FDI and FDI-related new jobs in the medium and long term. Relative to a situation of no change in the effective corporate tax rates in Ireland and other EU countries, we estimate that the global minimum effective corporate tax of 15 percent could result in a lower number of new FDI projects coming to Ireland by 3.4 percent over three years and 3.8 percent over ten years while the corresponding volume of new FDI invested could be lower by 12.3 percent after three years and by 14.6 percent after ten years. Further, we estimate that the number of FDIrelated new jobs associated with the number of new FDI projects, could be lower by 2.7 percent over three years and by 3.0 per cent over ten years while the number of FDI-related new jobs associated with the new FDI invested could be lower by 3.3 percent after three years and by 5.7 percent after ten years.
Keywords: F23; F43; H25; 330; Corporate taxation; foreign direct investment; employment